Hugh Wilford: America’s Great Game: The CIA’s Secret Arabists and the Shaping of the Modern Middle East (Czech Journal of International Relations, 2015)
Hugh Wilford: America’s Great Game: The CIA’s Secret Arabists and the Shaping of the Modern Middle East. 1. vydání. New York: Basic Books, 2013, 342 stran, ISBN 978-0-465-01965-6.